Financialisation, Indebted Workers and Labour Discipline: Empirical Evidence on Reduced Strike Activity in the European Union Countries - Barradas, R. (Dinâmia'CET-IUL Working Paper Nº2025/01, 2025)
Workers are being denoted by higher resignation and conformism and lesser claimant behaviour due to their lesser engagement in strikes, which indeliberately agrees with the proliferation of neoliberal policies and a corresponding deregulation and flexibilisation of labour relations that has led to a strong deterioration of labour conditions, a loss of labour rights and an increase in labour exploitation all over the world in the last five decades. Our argument to explain this puzzling paradox of worsening labour conditions yet less strike activity emphasises that as a result of their more financially fragile position, indebted workers evidence a more self-disciplined attitude and risk-averse behaviour in their workplaces in order to retain their jobs (and income) and honour their financial obligations, which then constrains their claims for higher wages and better labour conditions through engagement in strikes. This study assesses the influence of worker indebtedness on strike activity by performing a panel data econometric analysis from 1995 to 2022 that is focused on the European Union countries. Our results support our argument by confirming that worker indebtedness negatively impacts strike volume, strike participation and strike duration in the European Union countries. Our results also show that this negative impact is stronger in the European Union countries with the highest levels of worker indebtedness. In addition, our results corroborate that the growth in worker indebtedness is even one of the main drivers behind the decline of strike activity in the European Union countries since the mid-1990s.